Selected Metabolites Profiling of Staphylococcus aureus Following Exposure to Low Temperature and Elevated Sodium Chloride - Alreshidi, Mousa M. (Frontiers in Microbiology, 2020)
Staphylococcus aureus is one of the main foodborne pathogens that can cause food poisoning. Due to this reason, one of the essential aspects of food safety focuses on bacterial acclimation and proliferation under undesirable conditions. This study was aimed to determine the metabolic changes that can occur following exposure of S. aureus to either low temperature conditions or elevated concentrations of sodium chloride (NaCl). The results revealed that most of the metabolites measured were reduced in cold-stressed cells, when compared to reference controls. The major reduction was observed in nucleotides and organic acids, whereas mannitol was significantly increased in response to low temperature. However, when S. aureus was exposed to elevated NaCl, a significant increase was observed in metabolite abundance, particularly purine and pyrimidine bases along with organic acids. However, the majority of carbohydrates remained constant in the cells grown under ideal conditions and those exposed to elevated NaCl concentrations. Principal component analysis (PCA) of the metabolomic data indicated that both, prolonged cold stress and osmotic stress conditions, generated cells with different metabolite profiles, in comparison to the reference controls. These results provide evidence that, bacterial cells when exposed to low temperatures or high concentrations of NaCl, experience in situ homeostatic alterations to adapt to new environmental conditions. These data provided strong evidence supporting the hypothesis that specific changes in metabolic homeostasis were critical to the adaptive processes required for survival under changes in the environmental conditions.